2021
DOI: 10.1002/bse.2904
|View full text |Cite
|
Sign up to set email alerts
|

The impact of air pollution on the cost of debt financing: Evidence from the bond market

Abstract: This study investigates whether bond markets reflect firms' exposure to air pollution through an increased cost of debt financing; and, if so, whether firms can mitigate this air pollution penalty via effective governance and active monitoring. Using 1067 bonds issued by Chinese firms, we document a positive association between air pollution and the cost of debt financing, and this association is robust and economically meaningful. Specifically, with a one standard deviation increase in air pollution severity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 55 publications
1
20
0
Order By: Relevance
“…Based on the existing literature, the control variables in our research models largely included the factors that may affect the cost of debt. The adjusted-R 2 value in model (2) equaled 0.3318, which was similar to the 0.334 of Tan et al [ 16 ] and the 0.373 of Zhou et al [ 18 ], and was slightly higher than the 0.283 of Jung et al [ 10 ] and the 0.105 of Chen et al [ 9 ]. It indicated that the fitting degree of the model was acceptable.…”
Section: Resultssupporting
confidence: 63%
See 4 more Smart Citations
“…Based on the existing literature, the control variables in our research models largely included the factors that may affect the cost of debt. The adjusted-R 2 value in model (2) equaled 0.3318, which was similar to the 0.334 of Tan et al [ 16 ] and the 0.373 of Zhou et al [ 18 ], and was slightly higher than the 0.283 of Jung et al [ 10 ] and the 0.105 of Chen et al [ 9 ]. It indicated that the fitting degree of the model was acceptable.…”
Section: Resultssupporting
confidence: 63%
“…In response, creditors, including banks and other lending institutions, cannot ignore the environmental risk related to air pollution in the process of lending decision making [ 13 , 28 , 29 ] and prevent the air pollution-related default loss by revising debt contracts, such as raising the bond yields and interest rate as a response [ 10 , 12 , 30 ]. Tan et al [ 16 ] and Tan et al [ 15 ] also confirmed that firms in areas with serious air pollution face more significant debt financing constraints in the process of negotiation with banks due to a higher credit risk and financial uncertainty related to the environment. Consequently, we expect that firms located in areas with serious air pollution face a higher risk of environmental violations, and, thus, they need to afford higher debt costs in the process of debt financing.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 97%
See 3 more Smart Citations